Trends in relative weight over 1 year in low‐income urban youth. (30th October 2014) - Lawman, Hannah G.; Mallya, Giridhar; Veur, Stephanie Vander; McCoy, Tara; Colby, Lisa; Sanders, Tim; Wylie‐Rosett, Judith; Foster, Gary D.
<x xml:space="preserve">Abstract</x> Objectives Recent cross‐sectional data indicate the rates of childhood obesity are plateauing. Few large‐scale longitudinal data sets exist, particularly in low‐income and minority youth. The purpose of this study was to describe longitudinal changes in relative weight among a large sample of low‐income, minority youth over 1 year. Methods Participants were students from 56 schools in urban, low‐income environments. There were 17, 727 first‐ to sixth‐graders (64% African–American, 52% male) assessed at baseline, and 13, 305 youth (75.1%) were reassessed 1 year later at follow‐up. Measured height and weight were used to assess categorical (overweight, obesity, severe obesity) and continuous (BMI, percentile, z‐score) measures of relative weight. Results Longitudinal data showed that over 1 year, BMI percentile (95% CI.64‐–0.32, P < 0.001) and BMI z‐score (95% CI: –0.02‐–0.01, P < 0.001) were significantly lower compared to baseline. The prevalence of overweight and obesity was stable over 1 year. Most (86.0%) youth remained in the same weight category as baseline, 6.8% improved weight category, and 7.2% worsened weight category over 1 year. Conclusions These longitudinal data indicate that the relative weight of low‐income, urban youth is showing signs of a small improvement over a 1‐year follow‐up period. The rates of childhood obesity, however, remain remarkably high and require continued, creative public health efforts.